The Impact of Banking Security Features on Marketing Performance: Gold Indonesia 2045 - Pertiwi, Rizky Maulani; Sumahardi, Doddi; Indriani, Farida (Research Horizon, 2024)
The rise in fraud cases in the banking sector has led to negative market sentiment, which can affect market performance. Prospect Theory highlights how individuals make decisions under conditions of uncertainty. As we know, the development of advanced security features through technological innovation can drive sustainable economic growth, and transparent and reliable security features can help reduce this uncertainty. Therefore, banks must enhance the security features in their savings products. These bank security features include security tokens (hard tokens and soft tokens), Mobile Number Verification (one mobile number registered to one CIF), Safety Mode, cardless accounts (to avoid skimming and card trapping), and biometric validation. The problem is how security features in banking savings products can influence bank marketing in the context of negative market sentiment and Prospect Theory, while also supporting sustainability goals towards Gold Indonesia 2045. To address this issue, this research discusses thematic analysis of interviews to gain in-depth insights into the impact of security features on bank marketing and economic development. This study supports Indonesia's long-term vision by showing how banking security features contribute to the economic stability and growth necessary for achieving the goals set out for 2045.